Neoadjuvant chemotherapy is not a contraindication for nipple sparing mastectomy. Issue 5 (October 2015) - Santoro, Stefano; Loreti, Andrea; Cavaliere, Francesco; Costarelli, Leopoldo; La Pinta, Massimo; Manna, Elena; Mauri, Maria; Scavina, Paola; Santini, Elena; De Paula, Ugo; Toto, Vito; Fortunato, Lucio
Abstract Background Nipple-sparing mastectomy (NSM) has been recently implemented to improve cosmetic outcome after mastectomy, but it is rarely considered today after neoadjuvant chemotherapy (NCH). Patients and methods Among 275 NSMs performed from January 2007 to January 2015, 186 cases, with a minimum follow-up of 12 months, were carried out for invasive or intraductal carcinoma. Patients were considered for NSM if there were no clinical and radiological evidence of invasion or close proximity (<1 cm) to the nipple-areola complex (NAC). We compared patients operated with NSM after NCH (Group I N = 51) with those who underwent primary surgery (Group II, N = 135). Results At a median follow-up of 35 months, 166/186 patients were alive and disease-free (89.7%). Three local relapses (1.6%) were observed, all in the skin flap outside the NAC in Group I: (6%; p < 0.01). No NAC recurrences have been recorded, in either group. Nipple loss due to full thickness necrosis or resection for insufficient margins was recorded in 31 cases (17%); 12 in Group I (24%) and 19 in Group II (14%) (P = 0.1). This event decreased by half in the second part of the study (21/93 vs 10/93) (P = 0.03). Conclusions NSM after NCH is not associated with a statistically significant difference in terms of post-operative complications, total nipple loss for necrosis or margins, and results improve with experience. The loco-regional relapse rate was higher after NCH, yet it was consistent with traditional mastectomy in the high-risk setting. There is no need to avoid NSM after NCH for locally advanced cancers, if the retro-areolar margins of resection are clear at the time of surgery.